Is it possible to de-politicize and de-nationalize in the Olympics with a mechanism to transform the sports player to upgrade themselves - Chen, Z. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
The original part "Fundamental Principles" of the Olympic Charter states that the aim of the Olympic Movement is to contribute to the building of a peaceful and better world by educating young people through sporting activities without discrimination of any kind and with the Olympic spirit - mutual understanding in the spirit of friendship, solidarity and fair play. It can be highly summarized as "peace, friendship and progress". In each Olympic Games, athletes from different countries represent their countries in the competition, and some athletes become naturalized athletes, that is, athletes recruited by other countries, which has become a common phenomenon in sports such as football, basketball, baseball and table tennis. Many have questioned this: By admitting these athletes to the games, doesnt the IOC recognize the legitimacy of their status? The nationality of athletes is objective and historical, which is the basic content of their national identity. By allowing naturalized athletes to participate in the competition, isnt that the realization of their identity migration? Wouldnt their identity problems lead to new ones? From the perspective of athletes identity migration, will it cause the Olympic movement to lose the spirit of fairness? This paper analyzes the naturalization of international Olympic athletes by using the method of literature, case analysis and inductive deduction, and puts forward: We need to face up to the controversies caused by the value identification and identity transfer caused by the naturalization of athletes in the post-Olympic cycle, because the cross-cultural differences and even contradictions provide infinite possibilities and common meanings for the future exchanges between civilizations, inter-organizational exchanges and interpersonal communication that is, the discussion space of identity. In the International Olympic Committee, it is necessary to establish a new working mechanism to promote the coordination of athletes nationality migration and their national identity, so as to ensure the fairness of athletes participation, respect their self-identity and cultural identity, get rid of the political bondage of national identity, and empower athletes to confirm their identity through self-identification in international cooperation and competition.